1973
DOI: 10.1002/bjs.1800600213
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increased oxygen in acute limb ischaemia

Abstract: Acute hind‐limb ischaemia was produced in anaesthetized, ventilated dogs. During ischaemia the femoral venous oxygen tension fell markedly and both oxygen extraction and consumption appeared to increase. Oxygen at 2 ATA produced a relatively small increase in oxygen availability to the ischaemic tissues; femoral venous oxygen tension rose by 20 mm. Hg but oxygen extraction and consumption remained elevated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Hyperbaric oxygen has been used extensively for more than 50 years in the treatment of ischemic wounds, largely on an empirical basis, and with a paucity of controlled clinical trials. [8][9][10][11][12] Nevertheless, in some studies, hyperbaric oxygen has shown some clear-cut benefits for wound healing, [13][14][15] and it has been accepted as an efficacious therapy for diabetic ulcers in the setting of ischemia. [16][17][18] With the recognition of oxygen as a signaling molecule, and experimental observations that intermittent hyperbaric oxygen can induce growth factors and their receptors 19 and enhance growth-factor activities, 20 there has been an increased understanding of the mechanism of action of hyperbaric oxygen therapy.…”
mentioning
confidence: 99%
“…Hyperbaric oxygen has been used extensively for more than 50 years in the treatment of ischemic wounds, largely on an empirical basis, and with a paucity of controlled clinical trials. [8][9][10][11][12] Nevertheless, in some studies, hyperbaric oxygen has shown some clear-cut benefits for wound healing, [13][14][15] and it has been accepted as an efficacious therapy for diabetic ulcers in the setting of ischemia. [16][17][18] With the recognition of oxygen as a signaling molecule, and experimental observations that intermittent hyperbaric oxygen can induce growth factors and their receptors 19 and enhance growth-factor activities, 20 there has been an increased understanding of the mechanism of action of hyperbaric oxygen therapy.…”
mentioning
confidence: 99%